RAPD analysis of Asplenium adulterinum Milde from in vitro culture (Bangladesh Journal of Botany, 2022)
Asplenium adulterinum Milde represents one of the natural heritages which have to be protected due to their scientific importance. In the actual context of global warming with myriad effects on biodiversity, the ex-situ conservation of A. adulterinum should be a priority. The possibility to obtain genetically stable individuals through in vitro techniques is a requirement of ex situ conservation. The genetic similarity of A. adulterinum gametophytes maintained 8 years in vitro culture was assessed. Explants represented by gametophyte fragments were analyzed for genetic stability through RAPD. Close similarity (88.88%) was found between gametophytes maintained in the same conditions (medium, illumination, temperature, passages number).Bangladesh J. Bot. 51(2): 387-391, 2022 (June)